2x+13=-3x-20

Simple and best practice solution for 2x+13=-3x-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+13=-3x-20 equation:


Simplifying
2x + 13 = -3x + -20

Reorder the terms:
13 + 2x = -3x + -20

Reorder the terms:
13 + 2x = -20 + -3x

Solving
13 + 2x = -20 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
13 + 2x + 3x = -20 + -3x + 3x

Combine like terms: 2x + 3x = 5x
13 + 5x = -20 + -3x + 3x

Combine like terms: -3x + 3x = 0
13 + 5x = -20 + 0
13 + 5x = -20

Add '-13' to each side of the equation.
13 + -13 + 5x = -20 + -13

Combine like terms: 13 + -13 = 0
0 + 5x = -20 + -13
5x = -20 + -13

Combine like terms: -20 + -13 = -33
5x = -33

Divide each side by '5'.
x = -6.6

Simplifying
x = -6.6

See similar equations:

| -1/5x=-12 | | 5t-4=-14 | | (x*2)-9=x | | 8x+12=-6x-18 | | -6(m-23)=1 | | a+b=cfindb | | 8+5v=-8(-8v+8)+v | | 1/7-11=1/4x-14 | | 3.2+2.2x=3x | | x(2x-3)(4x+1)=0 | | 2x^2-2=45 | | -x-4.7=9 | | x/4=4/3 | | c=37+22h | | 12x-y=-10 | | 1/2r=3 | | c=22h+37 | | -36-8n=-3(3n+2)-5n | | f(x)=-3x^2-30x-82 | | 0.2x/x=2.5 | | xsquared-8x=20 | | 40m+0.25=25m+0.45 | | 9(k-2/3)=33=0 | | sinx=0.36736578268 | | (2)/(x^3)=0 | | X-kx+16=0 | | (2)/(x^3) | | 6x+2(100)=4x+40 | | X+x-27+x= | | 8x-(-3x-5)=5-x | | 3e=53 | | 0.4x+12.8=x-2.86 |

Equations solver categories